Wild & Chance - Zadoff, Allen (Wild & Chance, 2020)
When a girl wakes up trapped on a sinking ship with no memory of who she is, she has nothing but her instinct to survive. As she fights her way to freedom, she quickly discovers two incredible facts: She is a dog and she can understand human speech. Soon, she befriends a thirteen-year-old boy named Chance who gives her a name of her own -- Wild. But Wild and Chance find themselves running for their lives, pursued by relentless Animal Control officers. Joined by a mysterious hacker girl named Junebug, the unlikely trio fight for survival while trying to solve the mystery of Wild's extraordinary strength, super-intelligence, and high-tech collar.